The Students' Perception in Using Short Stories at EFL Classroom - Suzia Maretha; Ira Maisarah; Mega Fitri Wulandari (Journal of English for Specific Purposes in Indonesia (JESPI), 2023)
The inclusion of literature as one of the program's learning components English language, effective second-language usage, and effective use of English as a foreign language. Discuss the advantages of employing literature from different genres, such as poetry, theater, novels, or short stories, while teaching English in the decades past. The purpose of research is to identify short stories as a type of literature that may be utilized in English language learning or to improve language abilities. Because short stories have some advantages, like text that is interesting and can encourage students to learn the language Bitain, which is adapted to the level of understanding of the English language student, they have been chosen as a literary genre used as learning materials for the English language. The students’ perception in using short story of English language instruction can be seen from the perspectives of increased student vocabulary, text comprehension readings that allow students to translate the story into their own language, and students' ability to comprehend the historical context of the story.